Tinjauan Keabsahan Akad Perkawinan Mempelai Pria Penyandang Disabilitas Dihubungkan dengan Undang-Undang Perkawinan dan Hukum Islam - Karwiyah Karwiyah; Renny Supriyatni; Fatmi Utarie Nasution (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2023)
People with disabilities, namely the speech impaired as normal human beings, have sexual desires with the opposite sex and want to be able to carry out the sacred bonds of marriage. Confusion in society makes the marriage contract as one of the pillars of marriage carried out with various forms of sign language methods. The objective to be achieved in this study is to understand and determine legal certainty regarding the position and analyze the legal consequences of the marriage contract related to the Marriage Law and Islamic Law. This research uses a normative juridical approach method with research specifications that are analytical descriptions. The data collection techniques used are in the form of literature studies, field research using data collection techniques, and interviews so that the data analysis method used is qualitative juridical. The results showed that the marriage contract by the bridegroom with a disability is valid according to the Marriage Law and Islamic Law which is in line with the effectiveness of article 17 paragraph (3) of the Compilation of Islamic Law and jurisprudence. The legal consequences that arise according to the Marriage Law and Islamic Law are the relationship between husband and wife to their respective rights and obligations, the emergence of a relationship with their marital property, and the child born is a legal child and obtains the right of inheritance of his parents.